2021
DOI: 10.1108/jocm-12-2020-0366
|View full text |Cite
|
Sign up to set email alerts
|

Why and when do employees become more proactive under humble leaders? The roles of psychological need satisfaction and Chinese traditionality

Abstract: PurposeDrawing on self-determination theory, this study explored how leader humility affected employees' proactive behavior through satisfying their psychological needs for autonomy, competence and relatedness. Furthermore, based on a contingency view, this paper suggested Chinese traditionality as a significant boundary condition for the effects of leader humility.Design/methodology/approachData were collected from 465 employees and 111 direct supervisors in China using a three-wave, two-source design. Hierar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…It further confirmed the conclusion that idiosyncratic deals were always related to a positive work experience (e.g., meaningfulness of work). Previous research mainly used intermediary mechanisms, such as organizational-based self-esteem ( Wu et al, 2019 ), psychological capital ( Hu et al, 2018 ), and autonomous psychological needs ( Chen et al, 2021 ) to study the intermediary mechanism of leadership or organizational context on employee behavior. However, from the perspective of self-enhancement, this research provided a new idea for explaining the proactive behavior of new generation employees.…”
Section: Discussionmentioning
confidence: 99%
“…It further confirmed the conclusion that idiosyncratic deals were always related to a positive work experience (e.g., meaningfulness of work). Previous research mainly used intermediary mechanisms, such as organizational-based self-esteem ( Wu et al, 2019 ), psychological capital ( Hu et al, 2018 ), and autonomous psychological needs ( Chen et al, 2021 ) to study the intermediary mechanism of leadership or organizational context on employee behavior. However, from the perspective of self-enhancement, this research provided a new idea for explaining the proactive behavior of new generation employees.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that personalized charismatic leaders have disregard for their followers’ needs signifies a lack of empathy which is also associated with narcissism ( Tang et al, 2018 ). Moreover, personalized charismatic leaders exhibit a morally righteous “image” to enhance their influence and elevate their social status ( Chen et al, 2021 ). Such behavioral characteristics of exhibitionism and social assertiveness further corroborate their narcissistic tendencies.…”
Section: Theoretical Developmentmentioning
confidence: 99%
“…Subordinates’ dissatisfaction or negative attitudes toward their superiors will damage their interpersonal relationships, thus impeding their ability to execute their jobs effectively and advance their careers within the company ( Liu et al, 2010 ). Prior research has found that traditionality moderates the relationship between justice and organizational citizenship behaviors ( Farh et al, 1997 ), transformational leadership and leader effectiveness ( Spreitzer et al, 2005 ), inclusive leadership and follower’s taking charge ( Wang et al, 2020 ), leader humility and employees’ proactive behavior ( Chen et al, 2021 ), supervisor’s mentoring quality and subordinate’s proactive behavior ( Wu et al, 2019 ). Traditionality can also moderate the relationships among parental support, career decision-making self-efficacy and career adaptability ( Guan et al, 2016 ).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%